Access to business subsidies: What explains complementarities and persistency? - Heli Koski; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2010)
Our empirical analysis using an extensive database on the allocation of busi-ness subsidies in Finland during the years 2004-2008 finds that large firms are less likely to exit support system and more likely to continue receiving both support from one organization only and simultaneous support from multiple organizations. Large firms' propensity to transit between subsidies of different organizations is also higher than that of the smaller ones. Our study detects another interesting characteristic of the Finnish business subsidy system: the existence of agency-specific loyal customers. Firm size relates positively to the probability of a firm becoming the agency-specific customer of any public support provider, while the effect of other firm-level factors on this probability varies among the agencies. In addition to this, various parts of our analysis suggest that there is also a group of firms - comprising more likely larger firms - that tends to obtain support simultaneously from at least from two different organizations over several years. This finding is, as is the existence of agency-specific loyal customers, contrary to the basic principles of business subsidy system originally designed for providing temporary aid for companies.
Keywords: L53; O25; 330; public subsidies; complementarities; transitions; persistency